When does annual geriatric hip fracture mortality revert to baseline? - Bernstein, Joseph; Lee, Alexander; Ahn, Jaimo (Frontiers in Surgery, 2024)
BackgroundGeriatric hip fracture patients exhibit high mortality post-injury. It's unclear if and when mortality reverts to baseline. We therefore ask, When, if ever, does the mortality rate of geriatric hip fracture revert to the population-wide baseline rate? How does the mortality rate after geriatric hip fracture compare to the population norms? Understanding this timeline is crucial for assessing disease burden and guiding treatment plans.MethodsA cohort of 17,868 male patients aged 65–89 years treated for hip fracture within the VA healthcare system was studied. Patients were grouped by age at the time of fracture, and age-specific fractional survival was assessed annually for 10 years. For a comparison control group, a virtual cohort of 17,868 individuals, mirroring the age distribution of the patient group, was created and reduced over 10 cycles according to Social Security Administration expected mortality statistics.ResultsThe year-one mortality rate among fracture patients was 35.4%, compared to 6.3% in age-matched controls. By year ten, only 8.5% of the fracture patients remained alive, vs. 39.8% in the general population. The annual risk of dying for patients who survived past the first year was consistently in the range 19%–21% for all subsequent years.ConclusionHip fracture patients who survive the initial injury are still subject to annual mortality risk of approximately 20%, an elevation above population norms persisting for at least a decade. The data underscores the severity of geriatric hip fractures, and suggest that focusing one- or two-year survival rates may not fully capture the severity of the injury.